Hydrothermal synthesis of Bi2WO6 hierarchical flowers with their photonic and photocatalytic properties - Phattharanit Dumrongrojthanath (2018)
Bi2WO6hierarchical multi-layered flower-like assemblies were synthesized by a hydrothermal method at 180 °C for 24 h. XRD patterns were specified as pure orthorhombic well-crystallized Bi2WO6phase. Their FTIR spectra show main absorption bands at 400-1000 cm-1, assigned as the stretching modes of the Bi-O and W-O, and W-O-W bridging stretching modes. SEM analysis shows that the product was 3D hierarchical flower-like assemblies, constructed by orderly arranged 2D layers of nanoplates. The UV-visible absorption shows an absorbance in the ultraviolet region with 3.4 eV band gap. Photocatalytic activity of Bi2WO6hierarchical flowers was determined from the degradation of rhodamine-B by Xe light at 88% for 360 min irradiation. © 2012 Elsevier Ltd. All rights reserved.